Anti-signal recognition particle autoantibodies: marker of a necrotising myopathy. Issue 12 (5th May 2006) - Hengstman, G J D; ter Laak, H J; Vree Egberts, W T M; Lundberg, I E; Moutsopoulos, H M; Vencovsky, J; Doria, A; Mosca, M; van Venrooij, W J; van Engelen, B G M
Abstract : Objective: To elucidate the clinical importance of the anti-signal recognition particle (SRP) autoantibody in patients with myositis. Methods: Retrospective systematic assessment of the clinical, laboratory and histological characteristics of 23 anti-SRP-positive patients from six European centres. Data were compared with a large group of anti-SRP-negative patients with myositis published previously. Results: Clinically, patients with anti-SRP autoantibodies often had a severe symmetric proximal muscle weakness resulting in marked disability, dysphagia and highly elevated levels of serum creatine kinase. Three patients had typical dermatomyositis rashes. The disease was associated with the occurrence of extramuscular signs and symptoms including interstitial lung disease. No association was found with an increased risk of cardiac involvement, and the disease carried a reasonably favourable prognosis with most patients responding to treatment. None of the patients had the typical histological features of myositis. Most muscle biopsy specimens showed the presence of necrotic muscle fibres and no inflammatory infiltrates. Conclusions: Anti-SRP autoantibodies are associated with a syndrome of a necrotising myopathy in the spectrum of immune-mediated myopathies that differs from typical polymyositis. Further studies are needed to elucidate the pathogenesis and to clarify the role of the anti-SRP autoantibodies in this unique disease.